Strategi Kemitraan Antara KUD Musuk Dengan Peternak Dalam Meningkatkan Pendapatan Dan Kesejahteraan Peternak Sapi Perah Di Kabupaten Boyolali - Nugraheni Retnaningsih; Joko Setyo Basuki (Fakultas Pertanian Universitas Veteran Bangun Nusantara Sukoharjo, 2017)
This study aims to determine whether the strategic partnerships between cooperatives Musuk with dairy farmers in terms of attitudes, opinions, and perceptions of farmers has been running effectively to increase the income and welfare of dairy farmers in the sub-district Musuk, Boyolali. The method used is a case study that analyzed descriptively based on the Likert scale. Analysis of partnership strategy is done by using the measurements of Likert Scale. Data were collected using questionnaires, classified, scoring, tabulated, analyzed, and then interpreted to determine the partnership strategy implemented. The results of the analysis of strategic partnerships between cooperatives Musuk with dairy farmers said to be effective, because the values obtained on a Likert scale of 71%.Keywords: Strategi Partnership, KUDMusuk, Dairy farmers